A Numerical Simulation Approach for Sunspot Area Calculation - Saadi, S.; Chaker, A. (Engineering, Technology & Applied Science Research, 2018)
The aim of this paper is the numerical simulation of the sunspot area (SSA) and its location on the walls and on the floor of a room with a single window facing south. The input parameters of the calculation code are the geometry of the cell located in the site of Ksar Challala (35.1 N, 2.19 E, 800 m) in Algeria for the 21st of March, June and December. The SSA is a function of the window’s area, the date and time, the orientation of the room, the altitude and the azimuth of the sun. The obtained results show that the western wall is affected by the sun in the morning, the eastern wall in the afternoon, the floor and the north wall in the middle of the day. By increasing the window area from 1 m2 to 2 m2 we found that the SSA increases considerably.